Development of Modified Vo2Max Test Instrument - Muhamad Syamsul Taufik; Claudia Florina; Yasep Setiakarnawijaya; Budi Ariyanto Muslim; Widiastuti Widiastuti; Aridhotul Haqiyah (Universitas Pendidikan Indonesia, 2023)
The endurance component, namely Vo2max, is the part of physical fitness that supports important conditions. In terms of physical fitness, especially endurance, there is a need to develop test equipment to support and improve the performance requiring VO2max. This research was aimed to develop an instrument prototype, namely the Modified Vo2Max Test, using Ultrasonic sensor with lamp (LED 3 x 3 12VDC) and Buzzer (Piezzo 3-12 VDC). The set of this instrument consisted of four slaves. The placement of each LED sub-device depended on the need of the user. The basic circuit included sensors, WiFi modules, RGB LEDs, and a doorbell. The function of the sensor was to detect objects in the sensor area. The RGB LEDs acted as a signal when the sensor received stimuli. In addition, this instrument was made to facilitate the user movement in adding their skills according to their blindness. The valid test results showed an (rxy) value of 0.886. Compared to the table of r = 0.282, the value of rxy was higher with a sig value of 0.000 0.6. It concludes that the modified Vo2Max test is reliable. This Vo2max Futsal Prototype product is useful for players to examine their VO2max and physical fitness.